1997
DOI: 10.1104/pp.115.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Further Characterization of a Probable Plant Vacuolar Sorting Receptor

Abstract: The processes by which soluble proteins are sorted from the secretory pathway to the vacuolar compartments in plant cells are poorly understood. In contrast to receptormediated sorting of lysosomal proteins in mammalian cells, where the sorting determinant is a Man-6-P residue added to Asn-linked oligosaccharides (Kornfeld, 1992), plant vacuolar sorting is determined by sequences within the polypeptides themselves (Bednarek and Raikhel, 1991;Matsuoka and Nakamura, 1991;Neuhaus et al., 1991;Saalbach et al., 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
276
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(286 citation statements)
references
References 37 publications
6
276
0
2
Order By: Relevance
“…In mammalian cells, cargo receptors are recycled from their destination to the site of cargo binding (Seaman, 2005). VSR1 was found to localize to the TGN and the PVC (Paris et al, 1997;Sanderfoot et al, 1998); thus, VSR1 was also suggested to cycle between these organelles.…”
mentioning
confidence: 99%
“…In mammalian cells, cargo receptors are recycled from their destination to the site of cargo binding (Seaman, 2005). VSR1 was found to localize to the TGN and the PVC (Paris et al, 1997;Sanderfoot et al, 1998); thus, VSR1 was also suggested to cycle between these organelles.…”
mentioning
confidence: 99%
“…Research has indicated that some vacuolar cargo is packaged into clathrincoated vesicles through the action of the putative vacuolar cargo receptor AtELP/BP-80 (Ahmed et al, 1997;Paris et al, 1997;Sanderfoot et al, 1998). AtELP co-localizes with the v-SNARE AtVTI1a at the trans-Golgi network (Zheng et al, 1999b), and both proteins are probably packaged into clathrin-coated vesicles that travel to the PVC.…”
mentioning
confidence: 99%
“…Putative plant PVCs were identified using antibodies specific for the Arabidopsis (Arabidopsis thaliana) syntaxin Pep12p and the pea (Pisum sativum) vacuolar sorting receptor (VSR) BP-80 (Bassham et al, 1995;Conceicao et al, 1997;Paris et al, 1997). Studies on the relative distribution of VSR proteins between Golgi stacks and PVCs in various plant cells demonstrated that VSR proteins largely separated from Golgi markers and thus must be concentrated on PVCs under steady-state conditions (Li et al, 2002).…”
mentioning
confidence: 99%